(untitled) (Cambridge, 1994)
An economic history of Britain since 1700, in three volumes by 39 eminent historians and economists, this book will succeed the first edition of Floud and McCloskey' (published in 1981) as the leading textbook on its subject. The text has a firm economic basis, but emphasises the historical context and chronology and is written in straightforward and jargon-free English. It will appeal particularly to first and second year university students, but is also suitable for anyone interested in the history of the British economy. Volume 3 considers the period since 1939, that of relative economic decline and of increasing involvement with the European Community.
Keywords: Economic conditions; Britain